2016
DOI: 10.1111/xen.12259
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for isolating primary hepatocytes from mini pigs

Abstract: Successful porcine hepatocyte isolation is crucial for the development of bioartificial liver devices and hepatocyte transplantation. Serva collagenase NB grades are formulated collagenases that are suitable for various tissue isolation applications. N-acetylcysteine (NAC) can improve the viability of human hepatocytes. The aim of this study was to compare the effectiveness of two collagenases and effect of NAC on hepatocyte isolation from porcine liver tissue. Porcine hepatocytes were isolated using the perfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…With upgrade of commercial collagenase products such as Roche Liberase research grades and Serva collagenase NB grades, the isolations are more specific to the species, while the purity, viability, and yield of isolated primary hepatocytes are highly improved [4,18]. Except for the primary component, highly purified collagenaseand Ⅱmixture, we found that the amount of neutral protease thermolysin also determines the viability and cell yield, and especially the further success of spheroid formation.…”
Section: Hepatocyte Isolationmentioning
confidence: 88%
See 4 more Smart Citations
“…With upgrade of commercial collagenase products such as Roche Liberase research grades and Serva collagenase NB grades, the isolations are more specific to the species, while the purity, viability, and yield of isolated primary hepatocytes are highly improved [4,18]. Except for the primary component, highly purified collagenaseand Ⅱmixture, we found that the amount of neutral protease thermolysin also determines the viability and cell yield, and especially the further success of spheroid formation.…”
Section: Hepatocyte Isolationmentioning
confidence: 88%
“…It also has direct antioxidant properties and appears to have hepatoprotective effects against liver ischemia/reperfusion injury to improve the viability [9]. It has been proved to improve the viability and conserves the metabolic function of hepatocytes [4,18].…”
Section: Hepatocyte Isolationmentioning
confidence: 99%
See 3 more Smart Citations